A Simple Validated Method for the Estimation of Pepsin Activity in Microtiter Array for the INFOGEST Protocol - Maximiliano Ramm; Bárbara Alarcón-Zapata; Juan Monsalves; Luis Bustamante (Foods, 2023)
The INFOGEST protocol has been widely used as a static in-vitro simulation of gastrointestinal food digestion for bioaccessibility assessments on bioactive compounds. The standardization of the activity of several enzymes, such as pepsin, via UV-spectrophotometry of digested hemoglobin at 280 nm is a key step in the protocol. Standardization is a crucial stage since it is necessary to determine the quantity of enzyme to be added to the sample for digestion. However, this method is yet to be analytically validated; it requires quartz cuvettes and large volumes of samples and is time-consuming. Thus, we reviewed and adapted a well-known colorimetric method in microplates array by using the Folin–Ciocalteu reagent, and this study is the first to report for miniaturization of this method, the advantages of which include its automation, ease of use, the low volume of samples required, the minimal use of reagents, and speed. This method was compared to the traditional UV method, and the comparison results show no statistical difference between the inter day means for each group (p > 0.05). The proposed method was validated, showing high reproducibility (8% as inter-day CV) and statistically comparable results with the traditional UV spectrophotometric method.